Overview of Sales And Investment of Hard Drugs in Pharmacy “X” In Pamusian Village, Tarakan City With ABC Analysis For The Period Of October 2023 – October 2024 - Iqradiya, Azdyra; Heriani; Sari Wijayanti (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: This study aims to evaluate the sales and investment of hard drugs at Pharmacy